2021
DOI: 10.1016/j.heliyon.2021.e06198
|View full text |Cite
|
Sign up to set email alerts
|

Childhood caries management in the European Union: A cross-sectional study

Abstract: Dental caries is one of the most widespread childhood diseases worldwide, although it is largely preventable. In Europe, there is an observable difference between caries prevalence in Eastern and Western European states. This study aimed to gather data on the characteristics of publicly financed dental preventive services for children in European Union (EU) member states. Methods: Data on important indicators were collected through an online survey. National and international professional bodies specializing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…Although replicating the current study for other countries across the globe was beyond the scope of the study and would be complicated by differing health care finance structures and regulatory environments, a brief exploration of guidelines for FV internationally suggest variation may be present there as well. A survey study by Bencze et al found that the accessibility of clinical health prevention services such as FV application is limited and not free for children and varies across countries (39). A guideline on use of fluoride for prevention of ECC published by the European Archives of Pediatric Dentistry gives FV a "moderate" recommendation and recommends it primarily for children with higher risk for ECC (40) while Australian guidelines recommend FV for all children under 10 years of age (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although replicating the current study for other countries across the globe was beyond the scope of the study and would be complicated by differing health care finance structures and regulatory environments, a brief exploration of guidelines for FV internationally suggest variation may be present there as well. A survey study by Bencze et al found that the accessibility of clinical health prevention services such as FV application is limited and not free for children and varies across countries (39). A guideline on use of fluoride for prevention of ECC published by the European Archives of Pediatric Dentistry gives FV a "moderate" recommendation and recommends it primarily for children with higher risk for ECC (40) while Australian guidelines recommend FV for all children under 10 years of age (41).…”
Section: Discussionmentioning
confidence: 99%
“…Первинна профілактика хвороб пародонта та стоматологічних захворювань в цілому поки базується на програмах мінімізації факторів ризику. Виявлені в аналітичній епідеміології на основі використання анкетопитувальників індикатори ризику досить чітко можуть вказати, які дії повинні бути прийняті для підвищення ефективності профілактичних заходів [1,3,5].…”
Section: вступunclassified
“…Учасники дослідження та їх опікуни (батьки) відповіли на питання «Опитувальника стоматологічного для дітей і батьків» (свідоцтво про реєстрацію авторського права на твір, дата реєстрації 24.01.2020). Його було створено з урахуванням сучасних документів різних стоматологічних організацій, що регламентують оцінку здоров'я порожнини рота у дітей [1,5,8,9]. В осно-ву нашої анкети було покладено основні індикатори стоматологічного здоров'я дітей та підлітків проекту EGOHID ІІ (2008) та стоматологічний опитувальник ВООЗ (2013) [12,13].…”
Section: матеріали і методиunclassified
“…Tem etiologia multifatorial e consiste em uma associação entre uma dieta açucarada combinada ao acúmulo de biofilme, que favorece a atuação do metabolismo das bactérias bucais, que liberam ácidos, provocando a desmineralização. O processo se reverte quando diante da redução da exposição ao açúcar e prática adequada de higiene bucal (TSANG et al, 2019;BENCZE et al, 2021;SAMUEL;ACHARYA;RAO, 2020).…”
Section: Cárie Dentária Na Infânciaunclassified